NSAID and other analgesic use by endurance runners during training, competition and recovery - Joslin, J; Lloyd, JB; Kotlyar, T; Wojcik, SM (South African Journal of Sports Medicine, 2013)
Background. An increasing popularity of ultra-endurance events coupled with excessive or inappropriate non-steroidal anti-inflammatory drug (NSAID) use during such events could pose considerable potential risks to runners’ health. Objective. To evaluate the incidence of NSAID and other analgesic use in distance runners during training, competition and recovery. Methods. We performed an observational cross-sectional study at the Desert Race Across the Sand race (Colorado to Utah, USA) in June 2011 and the Empire State Marathon half-marathon, and relay races in Syracuse, NY, October 2011. A total of 27 ultramarathon runners and 46 marathon, half-marathon and marathon relay runners participated in the study. Surveys were distributed to runners during race registration. Self-reported use of common analgesic medications during training, racing and recovery was assessed. Results. Among all runners at all stages, NSAIDs were the most commonly used analgesic medication. NSAID use by ultramarathon runners compared with all other runners was similar during training (59% and 63%, respectively; χ2=0.008; p=0.93) and recovery (59% and 61%, respectively; χ2=0.007; p=0.93). However, ultramarathon runners were more likely than all other runners to use NSAIDs during the race (70% and 26%, respectively; χ2=11.76; p=0.0006). Conclusion. Despite undesirable side-effects associated with the use of NSAIDs, there was a high prevalence of use in all runners, particularly during training and recovery. NSAID use during the race was significantly greater in ultramarathon runners. Medical staff at endurance events need to be aware of, and prepared for potential complications related to the high use of NSAIDs in runners. Future efforts should focus on teaching runners about the undesirable effects of medication and emphasising alternatives to pain medication.